Study of high yielding crops cultivation in India using data mining techniques - Carmel Mary Belinda, M J; R, Umamaheswari; S, Alex David (International Journal of Engineering and Technology, 2018)
Data mining in agriculture is a modern and emerging research technique. Data mining provide many techniques like k means algorithm, support vector machine, association rule mining and Bayesian belief network [1]. This technique can be used in agriculture for various purposes. This paper describes about how association rules mining and apriori algorithm can be used in agriculture field. This paper also describes about soil, its types and crops grown in each type of soil. The technique that has been used here can be a rough set study, but like this many efficient techniques can be applied to solve many problems in agriculture.